Cotransplantation of Ex Vivo Expanded and Unexpanded Cord Blood Units in Immunodeficient Mice Using Insulin Growth Factor Binding Protein-2-Augmented Mesenchymal Cell Cocultures - Ong, L.M. (2014)
10.1016/j.bbmt.2012.01.001